A HISTORICAL QUEST FOR ETHICAL PRINCIPLES IN SPORT AS A NECESSARILY HUMANIZED PRACTICE (Fiep Bulletin - online, 2012)
The aim of this work was to present a historical perspective regarding possible particularities inherent in theideal of kalokagathia, of mens sana in corpore sano and of fair play, as references for a quest for ethical principles forsport, as a necessarily humanized practice. Such perspective being according to the referenced epochs, respectively,the Ancient period, the Medieval period, the Modern period and the Contemporary period of Humanity's History. Thetheoretic reference used to describe kalokagathia was based on the thinking of Plato (2003). To explain the aphorismmens sana in corpore sano it was important to compare various authors, such as Marinho (1945) and others. Finally,the theme of fair play and of the olympism of Coubertin was founded on the description occurring in the thinking ofCagigal (1996), among other authors. The complementary aspects of the subject were based on Huizinga (2000). Inconclusion, it is evident that it was possible to indicate the relationship that exists between such ethical principles,associated with the practice of modern and contemporary sport and practiced since the Ancient times of occidentalcivilization, always seeking to ennoble the necessary human perspective to be developed in the Being of Man.
Keywords: olympic ideal; humanized; kalokagathia; mens sana in corpore sano; fair play